Improvement of enzymatic saccharification of Populus and switchgrass by combined pretreatment with steam and wet disk milling. (April 2015) - Kumagai, Akio; Wu, Long; Iwamoto, Shinichiro; Lee, Seung-Hwan; Endo, Takashi; Rodriguez, Miguel; Mielenz, Jonathan R.
Abstract: To reduce the recalcitrance of lignocellulosic biomass for subsequent biological processing, we pretreated energy crop feedstocks with mild steam treatment (ST; 130 and 150 °C for 60 min) and wet disk milling (WDM). We tested two phylogenetically different, but typical energy crop feedstocks: Populus trichocarpa and switchgrass ( Panicum virgatum ). WDM after ST facilitated the fibrillation of both types of biomass, resulting in an increase of specific surface area, improved enzymatic saccharification yield, and decrease in cellulose crystallinity. After steam treatment at 150 °C followed by 17 cycles of WDM, enzymatic hydrolysis resulted in almost complete glucan to glucose conversion in both feedstocks. Highlights: Lignocellulosic biomass saccharification was improved by combination of ST and WDM. Mild-temperature ST limits the production of fermentation inhibitors. Mild-temperature ST facilitates fibrillation during WDM. Typical energy crop feedstocks Populus and switchgrass were used for evaluation. Almost complete glucose conversion was achieved in woody and herbaceous crops.